2008
DOI: 10.1007/s12147-008-9066-4
|View full text |Cite
|
Sign up to set email alerts
|

Flowers for Mom, a Tie for Dad: How Gender is Created on Mother’s and Father’s Day

Abstract: Mother's and Father's Day celebrations were investigated to understand how gender is created on these two occasions. Fifty-three heterosexual couples were interviewed about family holidays. Mother's Day was given more attention than Father's Day. Families spent more time celebrating; they were more likely to eat out, and were more likely to celebrate with others. Mothers were also more likely to receive gifts than fathers. The gendering of the holidays was reflected in the more stereotypical gifts received on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…This research shows that even though the gendered division of labour in the home, including parental roles, has changed, women receive more attention and gifts on Mother's Day than men on Father's Day. Similarly, the study shows that because motherhood is considered women's primary identity, women tend to have higher expectations for Mother's Day and suffer greater disappointment due to unmet expectations, as it is perceived to be a reflection of their performance as mothers (Cote and Deutsch 2008, p. 225). In contrast, because men's identity is not primarily linked to fatherhood they tend to enjoy Father's Day comparatively more (Cote and Deutsch 2008, p. 224).…”
Section: Rituals Of Love and (Market) Power: Valentine's Day And The mentioning
confidence: 97%
See 2 more Smart Citations
“…This research shows that even though the gendered division of labour in the home, including parental roles, has changed, women receive more attention and gifts on Mother's Day than men on Father's Day. Similarly, the study shows that because motherhood is considered women's primary identity, women tend to have higher expectations for Mother's Day and suffer greater disappointment due to unmet expectations, as it is perceived to be a reflection of their performance as mothers (Cote and Deutsch 2008, p. 225). In contrast, because men's identity is not primarily linked to fatherhood they tend to enjoy Father's Day comparatively more (Cote and Deutsch 2008, p. 224).…”
Section: Rituals Of Love and (Market) Power: Valentine's Day And The mentioning
confidence: 97%
“…Similarly, the study shows that because motherhood is considered women's primary identity, women tend to have higher expectations for Mother's Day and suffer greater disappointment due to unmet expectations, as it is perceived to be a reflection of their performance as mothers (Cote and Deutsch 2008, p. 225). In contrast, because men's identity is not primarily linked to fatherhood they tend to enjoy Father's Day comparatively more (Cote and Deutsch 2008, p. 224). Although, this study is limited in scope, what is important to note is that even when gender roles and employment patterns change, the gendered identities traditionally associated with the nuclear family take time to transform.…”
Section: Rituals Of Love and (Market) Power: Valentine's Day And The mentioning
confidence: 97%
See 1 more Smart Citation
“…To provide insights about societal expectations for parents, it is useful to analyze cultural objects associated with Mother's Day and Father's Day, occasions celebrated on two separate days, not on a singular Parents' Day. When Cote and Deutsch (2008) studied cultural objects associated with Mother's Day and Father's Day, namely the gifts, they found that mothers in the United States typically received flowers and a restaurant meal with their family, whereas fathers received ties or other masculine tokens of appreciation. Comic strips published on these two occasions (LaRossa, Jaret, Gadgil, & Wynn, 2000) have also shown a continued emphasis on traditional ideologies associated with motherhood and fatherhood.…”
Section: Introductionmentioning
confidence: 99%